Removal of emerging contaminants from water by using Fe-MOF composite as a sorbent - Chang, Fouzia; Memon, Najma; Memon, Shahabuddin; Chang, Abdul Sattar (Journal of the Iranian Chemical Society, 2021)
This study aims to solve the problem of water contamination. Fe-MOF composite material was prepared by the solvothermal method. Fe 3 O 4 core–shell magnetic nanoparticles covered with metal–organic frameworks (MOFs). The resulting composite Fe 3 O 4 @MIL-100 (Fe) was characterized with elemental analysis, FT-IR, SEM, EDS, and UV–Vis spectroscopy. For the removal of selected emerging contaminants from the aqueous solutions, various parameters were optimized (pH, concentration, adsorbent amount, and time) by using adsorbent Fe 3 O 4 @MIL-100 (Fe) with batch experiment. From results, it was concluded that the percent removal of selected drugs increases up to 85% within 3 h of contact time by increasing the amount of adsorbent. It helps to eliminate emerging contaminants from water at (pH 4 and 6). The drug adsorption was facilitated by electrostatic interactions, H-bonding, and π–π interaction represented in mechanisms. Pseudo-second-order kinetics and Freundlich models were used to explain the adsorption. Fe 3 O 4 @MIL-100 (Fe) adsorbent gives good percent removal and results compared with the literature.